Expert System Diagnosing Eye Diseases Using WEB-Based Forward Chaining Method - Ficeroy Derio (Journal of Intelligent Decision Support System (IDSS), 2020)
Health is very important for humans and also very important for the health of the five human senses, especially the sense of sight, namely the eyes. Eyes are windows to the world¸ this sentence seems to be the most appropriate to describe how important eyes are to human life. Often people ignore disturbances or complaints about their sense of sight and people think these complaints can go away on their own. Of course these complaints are early symptoms of eye disease. Because the above treatment is rare with some of its limitations, it is considered less helpful in solving existing problems, finally the idea arises of how the public knows eye diseases and their causes and how to overcome these diseases experienced in the eye without having to be an expert.